Evolution of Fructans in Aguamiel (Agave Sap) During the Plant Production Lifetime - Peralta-García, Ibeth; González-Muñoz, Fernando; Elena, Rodríguez-Alegría María; Sánchez-Flores, Alejandro; López Munguía, Agustín (Frontiers in Nutrition, 2020)
Aguamiel is the sap collected from agave, while pulque is the result of the natural fermentation of aguamiel. Despite its ancestral origin and numerous publications on pulque production, little is known about the evolution and concentration of sugars and fructo-oligosaccharides in aguamiel, either during its daily accumulation or through the agave production lifetime. In this study, we examined aguamiel composition in three agave plants during their productive lifetime (4 to 9 months). After each collection, the agave pine is scraped to induce aguamiel to flow into an internally created cavity (cajete), producing a residual bagasse (metzal). We found that the concentration of agave fructans and sucrose, as well as the fructan profile, change during the aguamiel production process. During the daily collection, a small amount of agave fructans released from the pine by scraping is drawn into the cajete with the first milliliters of sap where it is then diluted with the inflow of aguamiel. The main component of aguamiel is the sucrose produced in high concentration in the leaves through photosynthesis and then hydrolyzed in the cajete as aguamiel accumulates. We also describe how the fructan profile changes during the accumulation of aguamiel in the cajete. In addition to the varying amount of sucrose that is hydrolyzed in the aguamiel accumulated, we found that fructo-oligosaccharides are either diluted, consumed, or hydrolyzed, depending on the plant and its production stage, thus yielding different fructan profiles. New fructo-oligosaccharides are, in some cases, synthesized by bacteria present in aguamiel. These profiles were also observed in aguamiel collected from ten different plants in the same production region. We also found that a considerable amount of agave fructans is lost in metzal (bagasse), the agave material that is scraped and thrown away twice a day during the production process.